Visual Outcomes and Prognostic Factors of Successful Penetrating Keratoplasty in 0- to 7-Year-Old Children With Congenital Corneal Opacities. Issue 10 (October 2018) - Lin, Qi; Shi, Wei; Miao, Sen; Zhang, Yingnan; Li, Li; Pan, Zhiqiang
Abstract : Purpose: To determine the visual acuity and prognostic factors after successful penetrating keratoplasty (PK) in 0 to 7-year-old children with congenital corneal opacities. Methods: Sixty eyes (50 patients) with clear grafts after PK for congenital corneal opacity were enrolled and followed for 6 to 82 months. Visual acuity was measured using Teller acuity cards or Snellen charts, and cycloplegic refraction and flash visual-evoked potentials were measured. Mean age at primary keratoplasty was 2.5 ± 1.7 years. The mean follow-up duration was 18.9 ± 19.3 months. Results: Ambulatory vision (≥20/960) was achieved in 43 of 60 eyes (71.7%) at last follow-up, and 14 eyes (23.3%) had visual acuities >20/260. Compared with unilateral opacity eyes (58.8%), a significantly higher proportion of bilateral opacity eyes (88.5%) achieved ambulatory vision ( P = 0.012). Of all the surgical indications, unilateral sclerocornea was associated with the worst visual outcome—only 12.5% obtained ambulatory vision. Additional intraocular surgery was also associated with a reduced ambulatory visual acuity outcome. There were no significant differences in visual acuity among the different follow-up subgroups (<12 months, 12–36 months, and >36 months after operation; P = 0.928). Patients with bilateral opacity had a higher proportion of abnormal amplitude flash visual-evoked potentials than did patients with unilateral opacity ( P = 0.033). Ten of the 14 eyes that achieved 20/260 vision had corneal astigmatism ⩽3 diopters. Conclusions: Most of the clear grafts after PK in children with congenital corneal opacities achieved ambulatory vision. The visual outcome was better in binocular opacity cases than in monocular ones. Abstract : Supplemental Digital Content is Available in the Text.